Quality of neonatal care and outcome. Issue 1 (17th August 2007) - Acolet, D
Abstract : High quality of care in neonatology implies providing an appropriate level of care to well newborn babies as well as more specialised care for the few babies who need it. Audit, surveillance and outcome studies may not always capture the complexity of quality of care and its contribution to outcome, and a more focused approach to standards of care evaluation may be required. Future progress in this field in the UK would benefit from a more coordinated approach from different organisations to bring together expertise in large database, management and analysis, audit and a national profile for feedback, evidence-based guidelines and guidelines development skills, expertise in the practice of changes together with the promotion by credible perinatal authorities of clinical practice.